Counseling and Reservation Information System Integrated Public Service Complaints at DP3APPKB Salatiga - Maghtani, Bagas Erdo Al; Kristianto, Budhi (Jurnal Penelitian Pendidikan, 2025)
The purpose of this final task is to design and develop a website-based complaint and re-inspection information system, to implement a system that makes it easier for the public to submit complaints and conduct re-inspection online and to provide complaint data management features and a structured re-inspection schedule for DP3APPKB administrators. System Metode system development that will be created using CSS model and Visual Studio Code. Cascading Style Sheet (CSS) in its standard language. As defined in Quote and Wikipedia, CSS is a "code set used to define design and markup language", one of which is HTML. The results of the study resulted in an analysis of the public service complaint information system and the ongoing system as a means of system development. The results of the analysis of the completeness of the web-based public service complaint information system that can facilitate the public in making complaints and this software is designed using CSS and Visual Studio Code. Cascading Style Sheet (CSS) is a code editor and uses a MySQL database with Xampp tools. This Web-based Public Service Complaint Information System displays a list of complaints, complaints in the process of being repaired, evidence of complaints that have been repaired, and can download public complaint reports at the end of each month.